Calcineurin inhibitors or corticosteroids: Which is the best option for atopic dermatitis in children? (Portuguese Journal of Family Medicine and General Practice, 2010)
Objective: To compare the efficacy and safety of topical use of calcineurin inhibitors with corticosteroids in the treatment of atopic dermatitis (AD), in children. Data sources: MEDLINE database and evidence-based medicine websites. Review methods: The authors searched evidence-based reviews, guidelines, meta-analysis, systematic reviews and randomized controlled trials, using the MeSH terms: Dermatitis, Atopic; Tacrolimus, Pimecrolimus. The search was limited to articles published between January 2000 and August 2009, in English, French, Spanish and Portuguese, restricted to patients from zero to 18 years of age. International scales were used to describe the results: Investigators Global Assessment, Eczema Area and Severity Index and Childrens Dermatology Life Quality Index. Recommendation Taxonomy (SORT) of the American Family Physician was used to assess the level of evidence. Results: One guideline and one meta-analysis met the inclusion criteria from 76 studies obtained. Efficacy: The use of tacrolimus appears to be more effective in the treatment of moderate to severe AD, when compared to 1% hydrocortisone acetate. In the severe to very severe AD the use of 0,1% methylprednisolone aceponate have demonstrated to be superior. Safety: the use of tacrolimus was associated with more local adverse effects. Studies with pimecrolimus failed the inclusion criteria. Conclusions: From the available evidence Tacrolimus is more effective than 1% hydrocortisone acetate in the treatment of moderate to severe AD (SOR B). In severe or very severe exacerbation of AD the use of 0,1% methylprednisolone aceponate proved to be superior than tacrolimus (SOR A).
Keywords: Dermatitis; Atopic; Tacrolimus; Pimecrolimus; Child; Adolescent